Perceptions of students about the basic mathematics courses and their teachers at Philippine Normal University Isabela campus - Aguinaldo, Clemente M., Jr. (Animo Repository, 2013)
This study determined the college students’ perceptions about the basic mathematics courses and their teachers at Philippine Normal University Isabela Campus. These perceptions were then correlated to the mathematics performance of the students in their basic mathematics courses. The study made use of the descriptive type of research through survey and correlational methods. The 178 respondents were taken from the sophomore BEEd and BSEd Math students of PNU Isabela Campus. Questionnaires on students’ perceptions were used to gather the needed data. Findings disclosed that generally, the college students’ perception about the basic mathematics courses is of “average” difficulty while they perceived their teachers in the basic mathematics courses to be very satisfactory. Also, there is a significant negative correlation between the students’ perception about math and their mathematics performance. A significant low correlation exists between the students’ grades in Math 2 and their perception about their teachers.